Impact of ar flow rates on micro-structural properties of ws2 thin film by rf magnetron sputtering - Akhtaruzzaman M.; Shahiduzzaman M.; Amin N.; Muhammad G.; Islam M.A.; Sobayel Bin Rafiq K.; Sopian K. (MDPI AG, 2023)
Tungsten disulfide (WS2) thin films were deposited on soda-lime glass (SLG) substrates using radio frequency (RF) magnetron sputtering at different Ar flow rates (3 to 7 sccm). The effect of Ar flow rates on the structural, morphology, and electrical properties of the WS2 thin films was investigated thoroughly. Structural analysis exhibited that all the as-grown films showed the highest peak at (101) plane corresponds to rhombohedral phase. The crystalline size of the film ranged from 11.2 to 35.6 nm, while dislocation density ranged from 7.8 1014 to 26.29 1015 lines/m2. All these findings indicate that as-grown WS2 films are induced with various degrees of defects, which were visible in the FESEM images. FESEM images also identified the distorted crystallographic structure for all the films except the film deposited at 5 sccm of Ar gas flow rate. EDX analysis found that all the films were having a sulfur deficit and suggested that WS2 thin film bears edge defects in its structure. Further, electrical analysis confirms that tailoring of structural defects in WS2 thin film can be possible by the varying Ar gas flow rates. All these findings articulate that Ar gas flow rate is one of the important process parameters in RF magnetron sputtering that could affect the morphology, electrical properties, and structural properties of WS2 thin film. Finally, the simulation study validates the experimental results and encourages the use of WS2 as a buffer layer of CdTe-based solar cells. 2021 by the authors. Licensee MDPI, Basel, Switzerland.